Population Estimation and Habitat Characteristics of Anoa (Bubalus sp.) in Mount Kondoruang, Central Sulawesi - Dirham Dirham; Ongky Ongky; Manap Trianto; Yunita Messe (Biology, Medicine, & Natural Product Chemistry, 2026)
The anoa is a dwarf buffalo endemic to the Indonesian island of Sulawesi and several surrounding offshore islands. Despite its relatively small body size compared to other wild cattle, it is the largest wild terrestrial mammal native to Sulawesi. This study aims to estimate the population size and density of the anoa (Bubalus sp.) in Mount Kondoruang, Central Sulawesi, and to analyze the habitat characteristics that influence its distribution and occurrence. This project began with an information survey conducted from 8–15 June 2024 involving nature enthusiast groups (university student nature clubs) and local communities regarding the presence of the anoa on Mount Kondoruang. Data collection was carried out from 17–28 August 2024. Mount Kondoruang, also known as Kandela in Tojo Una-Una Regency, Central Sulawesi, Indonesia. Mount Kondoruang has an elevation of 2,870 meters above sea level and features diverse topography, ranging from hilly areas to mountainous terrain with slopes exceeding 15°, and is therefore designated as a Protected Forest area. The ecosystem types of Mount Kondoruang include savanna, lowland forest, lower montane forest, and upper montane forest. Mount Kondoruang remains an important habitat for the anoa, with individuals predominantly found in sub-montane forests. Habitat characteristics, particularly vegetation structure, elevation, temperature, and humidity, strongly influence its distribution. The limited population size and low juvenile detection indicate potential vulnerability, highlighting the need for continued monitoring and strengthened conservation efforts to ensure the species’ long-term survival.